Comorbidities, alone and in combination with D-dimer, as risk factors for recurrence after a first episode of unprovoked venous thromboembolism in the extended follow-up of the PROLONG study - Cosmi, Benilde; Legnani, Cristina; Tosetto, Alberto; Pengo, Vittorio; Ghirarduzzi, Angelo; Testa, Sophie; Prisco, Domenico; Poli, Daniela; Tripodi, Armando; Palareti, Gualtiero; for the PROLONG Investigators; (on behalf of FCSA, Italian Federation of Anticoagulation Clinics) (Thrombosis and Haemostasis, 2010)
The PROLONG randomised clinical trial showed that an abnormal D-dimer at one month after vitamin K antagonist (VKA) suspension for a first episode of unprovoked venous thromboembolism (VTE) is associated with a higher risk of recurrence. However, other patient characteristics, such as comorbidities, in combination with D-dimer could also influence the recurrence risk. It was the objective of this study to assess the predictive value of comorbidities and D-dimer in combination for recurrence after withdrawal of VKA in patients enrolled in the PROLONG study. On the day of VKA suspension, the presence of known (coronary, peripheral,cerebral) vascular disease, chronic inflammatory bowel disease, chronic obstructive pulmonary disease, autoimmune disease, diabetes, arterial hypertension, obesity and dyslipidaemias was registered. D-dimer was measured at 30 ± 10 days afterwards. The primary outcome was recurrent objectively documented VTE. Mean follow-up was 2.55 years. An abnormal D-dimer was observed in 44% (135/309) of patients with comorbidities and in 29% (87/299) of patients without (p=0.0003). An on-treatment analysis was conducted in 483 patients in whom VKAs were not resumed. In patients with a normal D-dimer, recurrences were observed in 14.3% (24/168) of patients with comorbidities and 10.8% (22/203) of subjects without (p=ns). In patients with an abnormal D-dimer, recurrences were observed in 24.6% (16/65) patients with comorbidities and 21.3% (10/47) of patients without (p=ns). Although abnormal D-dimer levels were significantly more frequent in patients with comorbidities, D-dimer was an independent risk factor for recurrence and the presence of comorbidities did not increase the risk of recurrence associated with an abnormal post-anticoagulation D-dimer.ClinicalTrials.gov number: NCT00264277
Keywords: Venous thromboembolism; risk factors; hypercoagulability; oral anticoagulants; atherosclerosis